The Impact of Earnings Per Share (EPS) and Net Profit Margin (NPM) on The Stock Price of PT Astra Agro Lestari Tbk - Hilyatu Siti Sa’adah; Hernawati, Euis (International Research & Development for Human Beings (IRDH), 2025)
This research explores the impact of Earnings Per Share (EPS) and Net Profit Margin (NPM) on the share price of PT. Astra Agro Lestari Tbk over the period from 2020 to 2024. This research utilises a quantitative approach, incorporating multiple linear regression analyses as a key component of the methodology. This research identifies earnings per share (X1) and net profit margins (X2) as independent variables, whereas stock price (Y) is categorised as the dependent variable. This research employs secondary data derived from the annual financial report of PT. Astra Agro Lestari Tbk, a publicly listed corporation on the IDX. The information was acquired through an exploration of the company's official website and www.idx.co.id. The research outcomes indicated that the Earnings Per Share (EPS) variable exerted no impact on the share price of PT. Astra Agro Lestari Tbk; variations in EPS, regardless of being positive or negative, did not affect the fluctuations in stock price. The Net Profit Margin (NPM) variable exerts a direct influence on the stock price of PT. Astra Agro Lestari Tbk; an elevation in NPM is associated with an increase in the value of the stock price. The Earnings Per Share (EPS) and Net Profit Margin (NPM) concurrently influence the share price of PT. Astra Agro Lestari Tbk.